Improving early warning systems for agricultural resilience in Africa - Coffey, Kevin; Haile, Menghestab; Halperin, Mea; Wamukoya, George; Hansen, James; Kinyangi, James; Tesfaye Fantaye, Kindie; Dinesh, Dhanush (2015)
Extreme climate events can undermine agriculture and rural development. Even in years when extreme events do not occur, the uncertainty that results from climate-related risk is an impediment to sustainable intensification of agriculture and adoption of climate-smart agricultural production practices. In an era of more frequent and more extreme weather events and climate shocks, enhanced early warning systems provide a key opportunity to curb erosion of development progress in rural sectors. This Info Note sets out recommendations to African policy makers for strengthening existing early warning systems and developing new systems in Africa.